Essays on Contemporary Events : The Psychology of Nazism. With a New Forward by Andrew Samuels - Jung, C. G. (Carl Gustav), 1875-1961 (Book collections on Project MUSE., 1989)
A discussion of the psychological and philosophical implications of events in Germany during and immediately following the Nazi period. The essays--""The Fight with the Shadow, "" ""Wotan, "" ""Psychotherapy Today, "" ""Psychotherapy and a Philosophy of Life, "" ""After the Catastrophe, "" and an Epilogue--are extracted from Volumes 10 and 16. Originally published in 1989. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback ed